On polars of Blaschke-Minkowski homomorphisms - Chang-Jian, Zhao (MATHEMATICA SCANDINAVICA, 2012)
In this paper we establish Minkowski, Brunn-Minkowski, and Aleksandrov-Fenchel type inequalities for the volume difference of polars of Blaschke-Minkowski homomorphisms.